Biophysical study on the role of staphyloxanthin in promoting desiccation tolerance in Staphylococcus aureus (2018)
Staphylococcus aureus is a Gram positive bacteria and an opportunistic pathogen responsible for a considerable amount of infections around the world, specifically it might take advantage of immunosuppressed patients in hospitals. For some years now, it has been registered that this microorganism is capable of tolerating desic- cated environments like walls, furniture surfaces or even surgical instruments. For this reason, understanding the mechanisms involved in desiccation tolerance is cru- cial in strategies to fight it back. S. aureus is known for the carotenoids it syn- thetizes, specially staphyloxanthin which is the major product. These molecules have been shown to provide certain levels of protection against different kinds of stress. In this thesis, a biophysical study was carried out in order to find the role staphyloxanthin plays in desiccation tolerance. Desiccation experiments along with carotenoids concentration analysis suggests correlation between staphyloxan- thin content and the capacity of the bacteria to survive this stress. FTIR spec- troscopy measurements were performed on lipids extracted from S. aureus under different conditions to estimate their thermotropic lipid phase behavior and although it showed that lipid cooperativity may be linked to staphyloxanthin concentration, there were very few data to conclude this correlation